Перспективи використання енергії водотоків технічних систем водопостачання та водовідведення - Vikchorew Yu.O.; IIyashenko A.P. (General Energy Institute of the National Academy of Sciences of Ukraine, 2002)
The analysis of the possibility and advisability of utilization of the hydro potential of the organized water flows of the different technical water supply systems and water outflow systems for purposes of local energy self supplying is given.